Event sponsorship factors towards purchasing intention / Nur Farhana Mohd Sah ... [et al.] - Mohd Sah, Nur Farhana; Wan Abdul Ghani, Wan Soraya; Abd Majid, Nurlisa Aina; Mohd Abas, Mohd Khalid (Universiti Teknologi MARA, 2020)
This study was conducted using empirical data to examine objectives by adopting the perception of attendees towards sponsors. Three distinct forms based on Tomalieh (2016) which proposed the relationship between brand knowledge, event sponsor-fit and attitude towards events to purchase intention was adapted. How consumers experience an event can also have a powerful influence over their purchasing intention behavior. Outcome of this study concludes that attitude towards the event is the most important factor and has a much more significant relationship towards purchase intention when compared with other variables. This factor refers to how event attendees perceive an event sponsor. This study adds to the body of knowledge by providing new data and empirical insight on the relationship between event sponsorship factors and purchase intention specifically for the event industry in Malaysia. For future studies, it is recommended that comparative studies with other industries as well as other developing and developed economies be carried out.